2020
DOI: 10.1016/j.dib.2020.106349
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of the phospholipidome and transcriptome of Campylobacter jejuni under different growth conditions

Abstract: The membrane phospholipid composition is not a stable bacterial characteristic but can change in response to altered environmental conditions. Here we provide the dataset of the phospholipidome and transcriptome of the microaerophilic human pathogen Campylobacter jejuni under different environmental conditions. These data have been used in Cao (2020), The unique phospholipidome of the enteric pathogen C. jejuni : Lysolipids are required for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Lysophospholipids are small bioactive lipid molecules characterized by a single carbon chain and a polar head group. It is hypothesized lysophospholipid allows C. jejuni to be motile under low O 2 conditions ( Cao et al., 2020a ). This is a significant observation considering the requirement of C. jejuni to adapt to the low oxygen deep in the mucus layer of the human GI tract.…”
Section: Jejuni Fitness and Virulence Factors: Role In Stmentioning
confidence: 99%
“…Lysophospholipids are small bioactive lipid molecules characterized by a single carbon chain and a polar head group. It is hypothesized lysophospholipid allows C. jejuni to be motile under low O 2 conditions ( Cao et al., 2020a ). This is a significant observation considering the requirement of C. jejuni to adapt to the low oxygen deep in the mucus layer of the human GI tract.…”
Section: Jejuni Fitness and Virulence Factors: Role In Stmentioning
confidence: 99%
“…A wide variety of LPLs were detected in C. jejuni, and the composition of these LPLs varied depending on environmental conditions. In particular, variations in oxygen levels can alter the composition of LPLs 83 . A previous study has shown that a high amount of LPLs is required for C. jejuni to maintain motility under oxygen-limited condition 83 .…”
Section: Metabolic Signatures Of Antibiotic Tolerance In C Jejunimentioning
confidence: 99%
“…In particular, variations in oxygen levels can alter the composition of LPLs 83 . A previous study has shown that a high amount of LPLs is required for C. jejuni to maintain motility under oxygen-limited condition 83 . Although the specific role of LPLs and their related mechanisms in bacterial stress response remain unclear, they are known to contribute to membrane curvature stress and stability, thereby affecting membrane permeability [84][85] .…”
Section: Metabolic Signatures Of Antibiotic Tolerance In C Jejunimentioning
confidence: 99%